2008
DOI: 10.1038/sj.bjc.6604410
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of topoisomerase-IIα in advanced ovarian cancer patients

Abstract: To our knowledge, very few data about the role of Topoisomerase IIa (TOPO-IIa), an enzyme involved in critical steps of tumour cell proliferation and chemoresistance are currently available in ovarian cancer patients. The aim of this study was to investigate the prognostic value of TOPO-IIa expression in a large, single institution series of 96 primary untreated advanced ovarian cancer patients admitted to the Gynecologic Oncology Unit, Catholic University of Campobasso and Rome. Immunohistochemistry was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…We found that high Topo‐II expression was an independent factor for reduced OS in patients with advanced NSCLC receiving amrubicin. Consistent with our observation, high Topo‐II expression has previously been shown to be significantly related to reduced OS in various cancers including urinary bladder carcinoma, breast cancer, gallbladder carcinoma, ovarian cancer, hepatocellular carcinoma, Hodgkin's lymphoma and prostate cancer . In an in vitro study, the expression levels of Topo‐IIα were found to be closely related to tumor cell proliferation and aggression .…”
Section: Discussionsupporting
confidence: 90%
“…We found that high Topo‐II expression was an independent factor for reduced OS in patients with advanced NSCLC receiving amrubicin. Consistent with our observation, high Topo‐II expression has previously been shown to be significantly related to reduced OS in various cancers including urinary bladder carcinoma, breast cancer, gallbladder carcinoma, ovarian cancer, hepatocellular carcinoma, Hodgkin's lymphoma and prostate cancer . In an in vitro study, the expression levels of Topo‐IIα were found to be closely related to tumor cell proliferation and aggression .…”
Section: Discussionsupporting
confidence: 90%
“…So far, numerous studies had mainly focused on TOP2A. Elevated TOP2A mRNA were observed in high grade ovarian cancers as well as advanced stage diseases, and patients with overexpression of nuclear TOP2A protein had a marked decreased OS [ 44 46 ]. In our study, for all EOC patients and serous patients, the TOP2A overexpression was associated with significantly worse OS, but insignificantly better OS in endomitrioid patients, maybe due to tumor heterogeneity as well as the small and unbalanced sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…(Topo II-α) has been extensively researched for its role as a molecular target of chemotherapy agents. Several studies have suggested that Topo II-α expression is related to response to anthracycline treatment for breast cancer (11)(12)(13), renal medullary carcinoma (14), ovarian carcinoma (15), salivary gland tumors (16,17), acute myeloid leukemia (18), Hodgkin's lymphoma (19), colorectal cancer (20), hepatocellular carcinoma (21), gallbladder carcinoma (22), prostate carcinoma (23), and other malignant tumors (24). Thus, these cancer types benefit from using Topo II-α as a prognostic marker, and also for individual tailored therapy.…”
Section: Expression Of Topoisomerase Ii-α Protein In Salivary Gland Tmentioning
confidence: 99%